Press shop die handling investigation through simulation / Azianti Ismail - Ismail, Azianti (2009)
This report has investigated the handling of the dies in a press shop of a major car company and in particular, the utilisation of the die transporter. The activity based simulation method of analysis particularly Extended Control Simulation Language (ECSL) has been applied to investigate the system behaviour in which to obtain solution that maximises the system performance. Activity Cycle Diagram (ACD) has been used as mechanism to both structure the model logic and develop the coding program of the system. A number of operating scenarios has been explored and performance measures such as queuing time, length and resource utilisation have been analysed. The effects of different operating scenarios such short pressing time and high volume dies have presented graphically to show the variation of results in the utilisation of the transporter. Hence, based on these analyses, recommended solutions are proposed to optimise the system performance which is the objective of the report. These investigations would be useful for the manufacturing engineers in applying the use of activity based simulation and the ACD in manufacturing systems.